Socioeconomic Status of Buffalo Rearing Farmers of Kashmir Valley - Dar, Parwaiz Ahmad; Khan, Azmat Alam; Shah, Anees Ahmad; Wani, Tasaduk; Qadri, Ishfaq Ahmad; Sheikh, Fayaz Ahmad (Indian Journal of Dairy Science, 2018)
A field survey was undertaken to record socio-economic status of buffalo rearers. Two geographically isolated districts with highest buffalo population viz, Anantnag in South Kashmir and Baramulla in North Kashmir were chosen. 200 respondents from each district were selected using random sampling technique and interviewed using a pre-structured questionare. The socio economic profile of the buffalo rearing farmers revealed that overall majority of the farmers had small sized family of 1-5 members and 74.25 percent lived in joint families. Majority (96.75%) of the buffalo rearers were schedule tribe gujjars with 51.00 percent of farmers in middle age group. Maximum proportion (82.50%) farmers were illiterate and 67.00 percent of farmers belonged to low income group. Main occupation of respondents Â was livestock, agriculture and labour. The overall majority 94.75 percent were marginal farmers with 1-2 buffaloes (72.00%) per house hold. Considerable number of the households (56.00 percent) were having small group (1-5 animals) followed by 26.50, 17.00, 0.50 percent as medium group (6-10 animals), large group (11-50 animals), very large group (>50 animals) respectively. 22.75 percent of the buffalo rearers kept 1-2 year old females followed by female of less than1 yr (12.50%), males less than1yr (10.50) and male of 1-2 yr of age (7.00%). The other livestock reared by buffalo rearers was cow (72.00%), sheep (24.00%), horse (18.00%), bull (14.50%) and goat (6.50%).